2021
DOI: 10.3390/met11020313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Successive Chemical and Thermochemical Treatments on Surface Features of Ti6Al4V Samples Manufactured by SLM

Abstract: Ti6Al4V samples, obtained by selective laser melting (SLM), were subjected to successive treatments: acid etching, chemical oxidation in hydrogen peroxide solution and thermochemical processing. The effect of temperature and time of acid etching on the surface roughness, morphology, topography and chemical and phase composition after the thermochemical treatment was studied. The surfaces were characterized by scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction and contact prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Tables 3 to 5: Experimental data of 3D-printed dental implants with a diameter of 3.4 mm, 3D-printed dental implants with a diameter of 4.3 mm and 3D-printed dogbone tensile specimen. Currently, most studies pay more attention to lower roughness values of < 5 μm, since it is suggested that Ra values of 3 to 5 μm will be more favourable for osteoblast responses than smooth surfaces with Ra values < 1 μm [29]- [31]. In the present study, dental implants and dogbone tensile specimens were fabricated using the DMLS technique.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 3 to 5: Experimental data of 3D-printed dental implants with a diameter of 3.4 mm, 3D-printed dental implants with a diameter of 4.3 mm and 3D-printed dogbone tensile specimen. Currently, most studies pay more attention to lower roughness values of < 5 μm, since it is suggested that Ra values of 3 to 5 μm will be more favourable for osteoblast responses than smooth surfaces with Ra values < 1 μm [29]- [31]. In the present study, dental implants and dogbone tensile specimens were fabricated using the DMLS technique.…”
Section: Resultsmentioning
confidence: 99%
“…- [31] Ti-Ta porous coating on Ti6Al4V by DED Anodic oxidation DED allows the production of a porous coating of Ti-Ta alloy on Ti6Al4V substrate. The elastic modulus is reduced compared to Ti6Al4V.…”
Section: Ti6al4v-slmmentioning
confidence: 99%
“…In addition, Ti is featured by its light weight or density (4.5 g/cm 3 ) compared to 7.9 g/cm 3 for 316 stainless steel and 8.3 g/cm 3 for cast CoCrMo alloys. Ti6Al4V is known for its excellent pitting corrosion resistance, tensile strength, biocompatibility, and excellent mechanical requirements [7]. Nevertheless, the high values of Young's modulus presented by fully dense Ti may show stress shielding that often evolves into bone resorption of the tissue surrounding the implant [8].…”
Section: Introductionmentioning
confidence: 99%